PENGGUNAAN DIKSI PADA DAFTAR MENU MAKANAN WARUNG DI MAKASSAR - Muh. Rizwan Indrahidayat R; Usman Usman (Universitas Negeri Makassar, 2022)
The use of diction in the food stall menu in Makassar. This study aims to: (1) describe the form of diction on the food stall menu list in Makassar, (2) describe the meaning of diction on the food stall menu list in Makassar, (3) describe the function of diction in the food stall menu list in Makassar. This type of research is qualitative research. The source of data in this study is the menu of a food stall in Makassar. The results of the study reveal the form of diction, types of meaning, and function of diction. The forms of diction used on food stalls in Makassar are basic words, affixes, reduplications, and compounding. There are nine types of meaning found in the use of diction in food stall menus in Makassar, namely lexical meaning, grammatical meaning, referential meaning, denotative meaning, connotative meaning, general meaning, special meaning, associative meaning, and idiomatical meaning. In addition, the diction function used on the food stall menu in Makassar, namely the function of providing information, the function of attraction, and the unique function.